Theory and method in higher education research. Volume 6 - Huisman, Jeroen; Tight, Malcolm (Emerald Publishing Limited, 2020)
Higher education research is a developing field internationally, which is attracting more and more researchers from a great variety of disciplinary backgrounds within and beyond higher education institutions. As such, it is an arena within which a wide range of theories, methods and methodologies are being applied. This volume of Theory and Method in Higher Education Research contains analyses and discussions of, amongst others, relational working, corpus linguistics, data dialogues, instrumental variables, participatory pedagogy, diverse participation, policy discourse, quality management and knowledge structures of research.
Includes index.
Keywords: Education, Higher -- Research.; Education -- Higher.; Higher & further education, tertiary education.; elektronické knihy; electronic books